Comparative Study on Mechanical Properties of a Tube-Crushing Dissipator and a Symmetric Tube-Crushing Dissipator - Wenkang Wang; Shaoqing Shi; Gaosheng Wang (Advances in Civil Engineering)
The tube-crushing dissipator is widely used in engineering, but it has the eccentricity problem. Therefore, a symmetric tube-crushing dissipator was proposed in this article, and quasistatic and dynamic tests were performed to compare mechanical properties of the tube-crushing dissipators and the symmetric tube-crushing dissipators. The results of the quasistatic tests show that the working force of the tube-crushing dissipators fluctuates around an average value which is about 20% smaller than the activation threshold after activation, while the working force fluctuates around an average value which is approximately equal to the activation threshold after activation. The results of the dynamic tests show that mean force at the crushing section of the tube-crushing dissipators and the symmetric tube-crushing dissipators increases with the increase of the impact velocity. Furthermore, the dynamic load-displacement curves are more volatile than those of the static tests. Therefore, dynamic tests which are more similar to the real working conditions of the dissipators are preferable over static tests. In addition, the metal tubes of the symmetric tube-crushing dissipators collapse vertically both in the quasistatic and dynamic tests; that is, the eccentricity problem of the tube-crushing dissipators is overcome by the symmetric tube-crushing dissipators.